Agro-well and pump diffusion in the dry zone of Sri Lanka: past trends, present status and future prospects - Kikuchi, M.; Weligamage, Parakrama; Barker, Randolph; Samad, M.; Kono, H.; Somaratne, H.M. (International Water Management Institute, 2003)
The use of shallow wells, equipped with small pumps, to lift groundwater has spread rapidly in many agricultural regions of tropical monsoonal Asia. In Sri Lanka, the rapid and pervasive invasion of agro-wells and pumps drew the attention of policymakers and researchers, but many questions were left unanswered due to lack of research in the area. This study aims to fill this gap in knowledge, based on observations and data obtained in field surveys conducted in major and minor irrigation schemes in the dry zone of Sri Lanka. This report gives the key findings of this study into the pattern, extent and causes of the spread and use of agro-wells and pumps in traditional villages and irrigated settlement schemes. It investigates farmer investments in agro-wells and pumps, the private internal rate of return to these investments, the economic viability of investments and incentives for farmers to make investments